Microstructure development in warm upset AM Ti64 - Szczepanik Stefan; Nikiel Piotr (Science of Sintering)
As AM Ti alloys generally contain porosity, for demanding applications it must be eliminated. HIP was reported, but it is expensive; accordingly forging by upsetting of EBM Ti6Al4V at 900°C was investigated. Strain rates of 0.01-1 s-1 were employed. In contrast to the as-printed material, porosity was not detected. From the plastometric tests the stress-true strain relationships were obtained and peak stresses were determined. Using the Simufact simulation program, details of the distribution of equivalent strains and temperatures were obtained. Comparison with wrought cast and printed materials is reported. The eventual microstructure consisted of alpha lamellae ranging in width from 1.81 to 2.34 μm, depending on strain rate and deformation, and beta formed in the interlamellar space during cooling in air. The hardness of the fully processed material was in the range of 293-304 HV1, independently of strain rate. This is to be compared with EBM Ti64, 316-360 HV0.3, and similarly processed cast wrought material, 350-365 HV0.3.